Human rights : confronting myths and misunderstandings - Fagan, Andrew, 1966- (Cheltenham, UK : Edward Elgar, 2009)
'This comprehensive book offers both an introduction and a critical analysis of enduring themes and issues in the contemporary theory and practice of human rights. Providing a multi-disciplinary analysis, it engages with philosophical, political and social approaches to the subject of human rights.''Andrew Fagan argues that the moral authority and practical efficacy of human rights are adversely affected by a range of myths and misunderstandings - from claims regarding the moral status of human rights as a fully comprehensive moral doctrine to the view that the possession of rights is antithetical to recognizing the importance of moral duties. The author also examines the claim made by some that human rights ultimately only exists as legal phenomena and that nation states are inherently hostile to the spirit of human rights. This book will challenge people to reconsider their understanding of human rights as a global moral outlook.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Human rights -- Philosophy; Responsibility; Citizenship -- Moral and ethical aspects; Abuse of rights